(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: Previous studies have demonstrated that geranyl metabolites, found mainly in marine organisms, exhibit interesting antimicrobial and antifungal activities. In addition, linear geranyl derivatives have been synthesized as drugs and reported cytotoxic and anticancer activities. Aims: Considering the biological testing and the structural features of these compounds, we evaluated seven linear geranylphenol derivatives on the human breast cancer cell line MDA-MB-231, and the human gastric cancer cell line MKN74. Results: We found that compounds 2, 5 and 7 were cytotoxic for both cancer cell lines. From them, the most potent was compound 2, with an IC50=7.5 μM for MKN74 cells, and compound 7, with an IC50=14.73 μM for MDA-MB-231 cells. By nuclear staining and inmunocytochemistry, we detected that the three compounds induced cell death, and by Western blot analysis, we observed a remarkable decrease in the expression of cyclin D1 and the retinoblastoma protein, key regulators of the cell cycle. Conclusion: Considering that compounds 2 and 7 were the most potent compounds inducing cell death, and were able to decrease the expression of retinoblastoma protein and cyclin D1, proteins usually altered in different types of cancers, they appear as promising therapeutic agents against cancer. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.486-500